Pragmatics and Media Framing: A Comparative Study of Anies Baswedan's Reporting in Kompas and Republika - Muhammad Fauzi; Mulyanti Syas; Muhammad Husni; Lidya Arman (Journal of Education Language and Innovation, 2026)
Mass media has a crucial role in shaping public perception through linguistic selection and news framing, especially in the run-up to political contests which often trigger polarization of viewpoints between media. This study aims to uncover the consistent use of pragmatic language and the dynamics of framing applied by Kompas and Republika in reporting on Anies Baswedan's progress during the crucial phase of 2022 to 2024. Through a qualitative approach with content analysis and critical discourse methods, data were collected from titles, leads, news bodies, opinion columns, and letters to the editor in both media, enriched by in-depth interviews with language aligners. The analysis integrates Searle's (1979) speech act theory, Leech's (1993) politeness principle, Pan and Kosicki's (1993) framing model, and Shoemaker and Reese's (2016) hierarchy of influence. The research findings reveal a systematic divergence: Kompas consistently dominates expressive speech acts of criticism and blame, often violating the maxims of acceptance and agreement, with a thematic frame linking policy to narratives of administrative irregularities. In contrast, Republika predominantly uses speech acts of praise and glorification, adheres to the maxims of generosity and humility, and constructs a frame emphasizing affirmation and leadership capabilities.